La "Vergogna": Annotazioni linguistiche per una ricerca nella Bibia - Tarocchi, Stefano (Studia Theologica Varsaviensia, 2017)
The term “shame” is none other than the evolution of spoken Latin verecundia language. So Dante Alighieri, the father of the Italian language: for “shame I mean three passions necessary to foundation of our good life: one is the Amazement; the other Modesty; the third is Shame: actually, Shame is a fear of being dishonored for a foul committed”. Two main families terms are used to describe the vocabulary of shame in the Greek Bible: 1) the verb αἰσχύνομαι (with the compound ἐπαισχύνομαι) and the noun αἰσχύνη [which corresponds to the Hebrew bóš], and the adverb αἰσχρῶς, derived by αἶσχος, „ugly” opposite of καλός; 2) the ὀνειδίζω verb [which corresponds to the Hebrew ḥārap, piel, „outrage”] and nouns ὄνειδος and ὀνειδισμός [translating Hebrew ḥerpâ].